Formulasi dan Karakterisasi Nanopartikel Kitosan Ekstrak Sari Buah Juwet (Syzygium cumini) menggunakan metode Gelasi Ionik: Formulation and characterization of Chitosan Nanoparticle of Juwet (Syzygium cumini) Fruit Extract Using Ionic Gelation Method - Wahida Hajrin; Wayan Cintya Ganes Budastra; Yohanes Juliantoni; Windah Anugrah Subaidah (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Syzygium cumini (S. cumini) fruits have a high potential to be developed as medicine because of their polyphenol content. Polyphenol is easily degraded so that its stability needs to be increased through the formation of nanoencapsulation. The aim of this study was to determine the formula of SBJ nanoparticles which has good characteristics. The formula was determined using a pseudoternary phase diagram based on the %transmittant and %EE. Nano SBJ was characterized for % transmittant ,% EE, polydispersity index, and zeta potential. The formula of Nano SBJ obtained chitosan, SBJ extract, and Na TPP were 0.347%, 0.627%, and 0.047%, respectively. The characterization of Nano SBJ were % EE was 30.72%, the mean diameter of particles was 138.1 ± 7.9 nm, PdI was 0.839 ± 0.043, and zeta potential was 34.9 ± 1.2 mV. Nano SBJ has nano-sized particles and has good stability, but low in entrapment efficiency.